(untitled) (Libya Journal of Geographical Studies, 2023)
Remote sensing and satellite images are useful scientific methods for geological investigations and to obtain direct geological surveys in the Bi’r Zlatan area, which belongs to the northern part of the Libyan Desert. Through the current study, ENVI 5 program was used to apply different digital processors to the Landsat 7 ETM+ image to determine the geological units. A supervised classification process was applied through a false color composite image with bands 741 was taken as a basis in the classification and cartographic processes and then compared with a published geological map of the same region to identify the names of the geological formations exposed. geological classified map of the study area was produced based on the principles of visual interpretation by calling the classification map in the GIS environment and then matched with the geological map in order to evaluate the accuracy of classifying with the regulation of the transparency level for the upper layer to 50% through ArcGIS 10, thus, the overall spatial accuracy of the obtained map was 70%, which was in agreement with the geological map of the study area. Finally, the digital geological map of the Bi’r Zaltan area can be linked to a wide database that is prepared for all the available geological information about this area. As well, this data can be updated in the future when any geological developments occur.